Pola Adaptasi dan Kemandirian Perempuan Kepala Keluarga Pasca Perceraian - Anita Florencya; Tubagus Hasanuddin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the social and economic conditions of women household heads after divorce. The method used in this study is to use a qualitative approach with fenomenology method with primary data collection through in-depth interviews with women heads of households in Harapan Jaya Village,South Panjang, Panjang District, Bandar Lampung with data analysis conducted descriptively. The results shown that divorce had a profound impact on the socio-economic conditions of woman household heads. This can be seen in the decline in family income and the presence of negative labeling on the status of a widow. To overcome this problem, women head of households do adaptation patterns to improve social conditions and increase income to meet needs. The adaptation patterns include being active in village activities, entrepreneurship and working as a laborer. By doing this adaptation pattern, it is expected that the quality of life of women household heads will be better and more independent.